The Evolution of Playfulness, Play and Play-Like Phenomena in Relation to Sexual Selection - Moraes, Yago Luksevicius; Valentova, Jaroslava Varella; Varella, Marco Antonio Correa (Frontiers in Psychology, 2022)
By conceptualizing Sexual Selection, Darwin showed a way to analyze intra-specific individual differences within an evolutionary perspective. Interestingly, Sexual Selection is often used to investigate the origins of sports, arts, humor, religion and other phenomena that, in several languages, are simply called “play”. Despite their manifested differences, these phenomena rely on shared psychological processes, including playfulness. Further, in such behaviors there is usually considerable individual variability, including sex differences, and positive relationship with mating success. However, Sexual Selection is rarely applied in the study of play, with exception to what is concerned as infant training behavior for adult sex roles. We offer an integrated grounding of playful phenomena aligning evolutionary propositions based on sexual selection, which might stimulate scientists to further explore playfulness within Darwinian framework of human behavior.